Semiotic analysis of Kemaliq phenomena as an effort to maintain culture and language in Ganti village community - Trijunianti, Nurul Fadila; Jaelani, Jaelani (Jurnal CULTURE (Culture, Language, and Literature Review), 2025)
This article examines the phenomenon of Kemaliq as a medium for maintaining language and culture. This research uses qualitative methods in data collection and analysis. The data collection techniques used observation, interview, and documentation. The results of this study indicate that Kemaliq is the language and culture of the Sasak community. First, Kemaliq can be used for various cultural activities, such as Nede, the ritual for asking for rain during the rice planting season. The local community will bring Dulang during the ritual. The Dulang serves as an iconic sign, representing gratitude and communal unity. Kemaliq can be used as a medium of education for the community regarding Kemaliq’s history and also as a place to learn Sasak literature. For example, at Kemaliq, there is a reading of Sasak literature that uses the Sasak Halus language, also called Linggih Kerame. The Linggih Kerame language is very rarely used in daily communication and is only used in certain activities and is only understood by a small part of the community. They can facilitate people who want to learn the Sasak Halus language, ensuring that traditional languages are not lost or forgotten amid language development in the modern era. This study demonstrates that the interaction of iconic codes within Kemaliq strengthens intergenerational cultural continuity and reinforces the collective identity of the Sasak community. The efforts made by the people of Ganti village to maintain the existence of their culture include forming an organization engaged in the preservation.